2018
DOI: 10.3390/app8091620
|View full text |Cite
|
Sign up to set email alerts
|

The Prostate Clinical Outlook (PCO) Classifier Application for Predicting Biochemical Recurrences in Patients Treated by Stereotactic Body Radiation Therapy (SBRT)

Abstract: (1) Background: Prostate cancer risk classifiers have been used for predicting surgical and radiation therapy outcomes; however, a classifier for predicting biochemical recurrence (BCR) in patients undergoing stereotactic body radiation therapy (SBRT) is not available. We attempted to develop a model that creates a risk classifier to predict BCR in patients considering SBRT. (2) Methods: We studied the outcomes of 809 patients treated with SBRT between August 2007 and November 2016. We used Cox regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The calibration was assessed based on the plot of predicted probabilities between the nomogram and actual probabilities (29). The calibration of smartphone addiction illustrated how its predictions were compared with the actual outcomes of the 593 smartphone users (34). The x-axis is the predicted value calculated using the SARR score, and the y-axis is the actual smartphone addiction probability of the smartphone users (35).…”
Section: The Sarr Score Based On the Logistic Regression-based Nomogrammentioning
confidence: 99%
“…The calibration was assessed based on the plot of predicted probabilities between the nomogram and actual probabilities (29). The calibration of smartphone addiction illustrated how its predictions were compared with the actual outcomes of the 593 smartphone users (34). The x-axis is the predicted value calculated using the SARR score, and the y-axis is the actual smartphone addiction probability of the smartphone users (35).…”
Section: The Sarr Score Based On the Logistic Regression-based Nomogrammentioning
confidence: 99%
“…A study of the prediction of type 2 diabetes and hypertension was conducted by [11] using density-based spatial clustering and synthetic minority over-sampling. The authors in [12] investigated the prediction of biochemical recurrences in patients treated by stereotactic body radiation therapy using prostate clinical outlook. Using Kruskal-Wallist test, regression model, Cuckoo search optimisation algorithm, and radial basis function neural network, a model was developed in [13] to determine whether the differences of tuberculosis prevalence rates for different income groups are statistically significant or not.…”
Section: Related Workmentioning
confidence: 99%
“…This showed significant improvement in precision, sensitivity, specificity, F1 score and accuracy, compared to existing methods support vector machine (SVM), multilayer perception (MLP), logistic regression, naïve bayes, and C4.5 using three benchmark datasets. S. K. Mun et al [9] in their manuscript entitled "The prostate clinical outlook (PCO) classifier application for predicting biochemical recurrences in patients treated by stereotactic body radiation therapy (SBRT)", implemented a prostate clinical outlook classifier for the classification of biochemical recurrence in patients undergoing stereotactic body radiation therapy. It concluded that four parameters are effective in increasing the prediction accuracy: Gleason scores, pretreatment prostate specific antigen, clinical radiological staging and age.…”
Section: Workmentioning
confidence: 99%